lead-acid batteries
Patent Information
- Application Number
- JP2025058846
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
Smart Images

Figure 2026166103000001_ABST
Abstract
Description
[Technical Field]
[0001] This disclosure relates to lead-acid batteries. [Background technology]
[0002] Patent Document 1 describes a lead-acid battery comprising a current collector, a positive electrode plate having a positive electrode material supported by the current collector, and a negative electrode plate, wherein the total pore volume per unit mass of the positive electrode material is 0.167 cm³. 3 The value is less than or equal to / g, and the positive electrode material contains fibers, and the average specific surface area of the fibers measured by the BET method using krypton gas as the adsorption gas is 0.25 m². 2 They are proposing a lead-acid battery that is rated at or above / g. [Prior art documents] [Patent Documents]
[0003] [Patent Document 1] Japanese Patent Publication No. 2019-67741 [Overview of the project] [Problems that the invention aims to solve]
[0004] With the advent of OTA (Over The Air) technology, the load on lead-acid batteries is increasing. Repeated charging and discharging can easily cause the positive electrode material of lead-acid batteries to soften and detach, leading to a premature end of life for the battery. Therefore, a technology has been disclosed that can improve the life characteristics of lead-acid batteries by adding fibers with a large specific surface area to the positive electrode material (see Patent Document 1). However, there is still room for improvement in life performance when deep charging and discharging (hereinafter also referred to as "deep discharge cycles") is repeated (hereinafter also referred to as "deep discharge life"). [Means for solving the problem]
[0005] One aspect of the present disclosure relates to a lead-acid battery comprising a positive electrode plate, a negative electrode plate, an electrolytic solution, and a separator interposed between the positive electrode plate and the negative electrode plate, wherein the positive electrode plate contains a positive electrode material, the positive electrode material contains fibers, and a maximum height Rz of a surface of the fibers is 0.17 μm or more and 1.9 μm or less.
Effects of the Invention
[0006] The lead-acid battery according to the present invention can ensure favorable life performance when charging and discharging with a deep depth of discharge are repeated.
Brief Description of the Drawings
[0007] [Figure 1] It is a partially cutaway perspective view showing the external appearance and internal structure of a lead-acid battery according to one embodiment of the present invention.
Modes for Carrying Out the Invention
[0008] Hereinafter, embodiments of the present disclosure will be described with reference to examples, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values and materials may be exemplified, but other numerical values and materials may be applied as long as the effects of the present disclosure can be obtained. In this specification, the description "numerical value A to numerical value B" includes numerical value A and numerical value B, and can be read as "numerical value A or more and numerical value B or less". In the following description, when lower limits and upper limits of numerical values relating to specific physical properties, conditions and the like are exemplified, any of the exemplified lower limits and any of the exemplified upper limits can be arbitrarily combined as long as the lower limit does not exceed the upper limit. When a plurality of materials are exemplified, one of them may be selected and used alone, or two or more thereof may be used in combination.
[0009] Further, the present disclosure includes combinations of the matters described in two or more claims arbitrarily selected from the plurality of claims described in the appended claims. That is, as long as no technical contradiction arises, the matters described in two or more claims arbitrarily selected from the plurality of claims described in the appended claims can be combined.
[0010] (1) A lead-acid battery according to an embodiment of the present disclosure comprises a positive electrode plate, a negative electrode plate, an electrolyte, and a separator interposed between the positive electrode plate and the negative electrode plate. The positive electrode plate includes a positive electrode material. The positive electrode material includes fibers, and the maximum surface height Rz of the fibers is 0.17 μm or more and 1.9 μm or less.
[0011] When deep discharge cycles are repeated, the positive electrode material is prone to softening and detachment. In the charged state, the positive electrode material forms a network of bonded lead dioxide particles. When lead dioxide is converted to lead sulfate through the charge-discharge reaction, its volume expands by approximately 1.5 times. When deep discharge cycles are repeated, the bonds between the lead compound particles in the positive electrode material usually break, and some of the lead compound becomes isolated. As a result, softening progresses from the surface of the positive electrode plate, and detachment of the positive electrode material occurs.
[0012] In contrast, when the positive electrode material contains fibers, softening and shedding of the positive electrode material are suppressed, ensuring a good deep discharge life. The deep discharge life can be evaluated using the "Life Test Method" described later.
[0013] However, if there are deep wrinkles on the surface of the fibers, the charge-discharge reaction may be inhibited by the positive electrode material becoming trapped in the space inside the wrinkles, or by sulfate ions being trapped. Because the space inside the wrinkles has low ion diffusion, if the positive electrode material becomes trapped in such a space, the uptake of sulfate ions by the positive electrode material and the release of sulfate ions from the positive electrode material become difficult to carry out. Therefore, in the space inside the wrinkles and in the vicinity of wrinkles that are susceptible to the effects of wrinkles, the charge-discharge reaction by the positive electrode material does not proceed sufficiently, leading to a decrease in the capacity of the lead-acid battery. Even if the positive electrode material does not become trapped in the space inside the wrinkles, sulfate ions present inside the wrinkles interact with the wrinkle walls and become difficult to diffuse, so sulfate ions are not effectively utilized and the charge-discharge reaction may be inhibited. In particular, when the DOD is deep, the sulfate ion concentration in the electrolyte becomes low, so the effect of wrinkles becomes more pronounced, and the discharge reaction is especially easily inhibited. As a result, the deep discharge life tends to decrease.
[0014] In the lead-acid battery described in (1) above, since the maximum surface height Rz of the fibers is 1.9 μm or less, the surface irregularities caused by wrinkles in the fibers are sufficiently small and are not thought to form enough space for a large amount of positive electrode material and sulfate ions to enter. Furthermore, when the maximum surface height Rz of the fibers is 0.17 μm or more, it can be said that the surface of the fibers has irregularities sufficient to exhibit a high anchoring effect. Wrinkles on the surface of the fibers can enhance the effect of the fibers in suppressing the detachment of positive electrode material from the positive electrode plate. In other words, when the maximum height Rz is between 0.17 μm and 1.9 μm, the charge-discharge reaction is less likely to be inhibited by the fibers, and a high anchoring effect is also exhibited, making it possible to ensure a good deep discharge life.
[0015] If the maximum surface height Rz of the fiber exceeds 1.9 μm, the surface irregularities caused by wrinkles are thought to become too large. As a result, a large amount of positive electrode material and sulfate ions can enter the spaces inside the wrinkles, which may inhibit the charge-discharge reaction. If the maximum surface height Rz of the fiber is less than 0.17 μm, the irregularities formed on the fiber surface are too small, and a high anchoring effect cannot be obtained. In this case, although the charge-discharge reaction is not significantly inhibited by the fiber, the effect of the fiber in suppressing the softening and detachment of the positive electrode material is reduced.
[0016] As described above, when the maximum surface height Rz of the fiber is between 0.17 μm and 1.9 μm, the fiber surface can be said to have a degree of unevenness that does not have excessively large wrinkles, while at the same time enhancing the fiber's reinforcing effect.
[0017] The maximum surface height Rz of the fiber may be 0.2 μm or more, or 0.3 μm or more. The maximum surface height Rz of the fiber may be 1.8 μm or less, 1.7 μm or less, 1.6 μm or less, or 1.5 μm or less.
[0018] The maximum surface height Rz of the fibers may be adjusted beforehand by surface treatment of the fibers. The maximum surface height Rz of fibers whose surface height Rz has not been adjusted may be adjusted by a predetermined method. The maximum surface height Rz of the fibers may be adjusted during the manufacturing process of the lead-acid battery.
[0019] One method for adjusting the maximum surface height Rz of a fiber is chemical treatment, which modifies the fiber surface using chemicals such as acids and alkalis. Other methods for adjusting the maximum surface height Rz of a fiber include plasma treatment, which modifies the fiber surface using plasma; corona treatment, which modifies the fiber surface using high-voltage discharge; and UV irradiation treatment, which modifies the fiber surface using ultraviolet light. Yet another method is sandblasting, which involves impacting the fiber with fine powder harder than the fiber itself.
[0020] For example, when performing plasma treatment, corona treatment, or UV irradiation as a method for treating the surface of fibers, the maximum height Rz of the fiber surface may be adjusted by changing the output value of the processing apparatus, the processing time, or both. In sandblasting, the speed of the fine powder impacting the fibers and the processing time can also be changed. The maximum height Rz may also be controlled by the heat treatment conditions of the fibers, the polishing conditions of the fiber surface, etc.
[0021] (Method for measuring the maximum height Rz on the surface of a fiber) The maximum surface height Rz (and the average surface roughness Ra, described later) of the fibers is determined for fibers taken from the positive electrode material of a fully charged lead-acid battery by the following procedure. The method for taking the fibers will be described later.
[0022] In accordance with ISO 4287:1997, the maximum surface height Rz of the fiber is determined using a laser microscope. Specifically, an image for analysis is acquired with a 20x objective lens. The acquired image is then subjected to automatic noise reduction and tilt correction using an analysis application. The line roughness is measured using the analysis application to determine the maximum surface height Rz of the fiber. The analysis is performed with all filter conditions (F calculation, S filter, L filter) set to none.
[0023] The following can be used as measuring devices: Laser microscope: VK-X3000, manufactured by Keyence Corporation. Objective lens: Nikon Corporation, Plan x20 NA 0.46 WD 3.1mm Analysis application: VK-A3, manufactured by Keyence Corporation.
[0024] The following can be used as measuring devices. Preferred measuring conditions are also shown below. Measuring device: Shimadzu Corporation, TriStar II 3020 series Adsorption gas: Krypton gas with a purity of 99.99% or higher. Adsorption temperature: -196℃
[0025] (2) In the lead-acid battery described in (1) above, the surface area of the fibers per gram of positive electrode material is 1.35 cm². 2 It is preferable that the above conditions are met.
[0026] To prevent softening and detachment of the positive electrode material, it is considered effective to sufficiently increase the contact area between the fibers contained in the positive electrode material and the positive electrode material itself.
[0027] The surface area of the fibers per gram of positive electrode material is 1.35 cm². 2 In the above case, the contact area between the lead compound constituting the positive electrode material and the fibers is also approximately 1.35 cm² per gram of positive electrode material. 2It can be considered to be as above. The fibers and the lead compound are entangled with each other over such a large contact area, which also enhances the anchoring effect by the fibers, increases the binding force between lead compounds, and is considered to significantly improve the deep discharge life of the lead-acid battery.
[0028] The surface area of the fibers per 1 g of the positive electrode material is calculated as the surface area possessed by the fibers contained in 1 g of the positive electrode material. Specifically, X g of the positive electrode material contains Y g of fibers, and the surface area of the Y g of fibers is Z cm 2 , the surface area of the fibers per 1 g of the positive electrode material is Z / X (cm 2 / g). Assuming that the fiber has a cylindrical shape with a length L, when the average fiber diameter is D, the surface area of one fiber is calculated as πDL. When N fibers are contained in W g of the positive electrode material, the surface area of the fibers per 1 g of the positive electrode material is calculated as NπDL / W. Further, the volume of the cylinder having a surface area of NπDL is π(D / 2) 2 NL, therefore, in the case of a fiber density d (g / cm 3 ), if the mass w of the fibers contained in W g of the positive electrode material and the average fiber diameter D are known, from the relational expression of w / d = π(D / 2) 2 NL, NL (= w / d · π(D / 2) 2 ) can be determined, and NπDL / W can be calculated.
[0029] Here, the fiber density d (g / cm 3 ) is a standard fiber density described in books or technical documents, and a resin sample may be prepared and measured in accordance with "Plastics - Methods for measuring the density and specific gravity of non-foamed plastics" specified in JIS K 7112:1999. For example, the "3rd Edition Fiber Handbook" edited by The Society of Fiber Science and Technology, Japan and published by Maruzen Publishing Co., Ltd. (2004) lists the specific gravity of fibers. The numerical value of the specific gravity of a fiber matches the numerical value of the fiber density d. When there is a range in the fiber density or specific gravity described in books or technical documents, the average value of the described numerical range may be used as the fiber density d. For example, the "3rd Edition Fiber Handbook" states that the specific gravity of acrylic fibers is 1.14 to 1.17. In that case, the fiber density d (g / cm3 ) is 1.155 ≈ 1.16 (g / cm³) 3 ) can be considered as such.
[0030] The type of resin constituting the fibers contained in the positive electrode material can be identified by analyzing the fibers recovered from the positive electrode material using the method described in JIS L 1030-1:2024. The fibers may be recovered by pulling them out of the positive electrode material with tweezers, or by recovering them from the residue after dissolving the lead compounds contained in the positive electrode material.
[0031] The surface area of the fibers per gram of positive electrode material is 1.67 cm², which is the point at which the anchoring effect by the fibers is higher. 2 It is more preferable that the length be greater than or equal to 1.70 cm. 2 or more, or 2.00 cm 2 The above is also acceptable. The surface area of the fibers per gram of positive electrode material is 5.00 cm². 2 The following is preferable, and by controlling it within this range, sufficient conductive paths can be secured within the positive electrode material, thereby improving the capacity retention rate.
[0032] (3) In the lead-acid battery described in (1) or (2) above, it is preferable that the maximum surface height Rz of the fibers is 1.4 μm or less. When the maximum surface height Rz of the fibers is within the above range, inhibition of the charge-discharge reaction by the fibers is significantly suppressed, while the anchoring effect of the fibers is fully expressed. As a result, a better deep discharge life can be ensured. In addition, when repeating charge-discharge cycles at a shallower discharge depth, the charge-discharge reaction is less likely to be inhibited by the fibers, which makes it easier to improve the capacity retention rate.
[0033] The maximum surface height Rz of the fiber may be 0.17 μm or more, or 0.6 μm or more. The maximum surface height Rz of the fiber may be 1.2 μm or less, or 1.0 μm or less. From the viewpoint of obtaining better deep discharge lifetime and capacity retention rate, the maximum surface height Rz of the fiber may be 0.6 μm or more and 1.2 μm or less.
[0034] (4) In the lead-acid battery described in any one of (1) to (3) above, the average fiber diameter is preferably 1 μm or more and 9 μm or less. More preferably, the average fiber diameter is preferably 1 μm or more and 8 μm or less, and may be 4 μm or more and 9 μm or less, or 4 μm or more and 8 μm or less. Such fibers have sufficiently high mechanical strength and can have a large specific surface area. Also, even with the same amount of fiber, the number of fibers increases, so the structure in which the fibers are interwoven within the positive electrode material tends to be formed. Therefore, the contact area between the fibers and the positive electrode material becomes sufficiently large, and it becomes possible to ensure a good deep discharge life.
[0035] (5) In the lead-acid battery described in any one of (1) to (4) above, the surface area of the fibers per gram of the positive electrode material is 3.00 cm². 2 The above is preferable. In terms of further enhancing the anchoring effect by the fibers, the surface area of the fibers per gram of positive electrode material should be 3.00 cm². 2 It is more preferable that the length be greater than or equal to 3.40 cm. 2 Above, or 3.70cm 2 Over 4.00cm 2 The above is also acceptable. Furthermore, it is believed that the entanglement of the fibers and lead compounds over a larger contact area enhances the anchoring effect of the fibers, increases the bonding strength between the lead compounds, and significantly improves the deep discharge life of the lead-acid battery.
[0036] The lead-acid battery according to an embodiment of the present invention will be described in more detail below with reference to the drawings. However, the present invention is not limited to the following embodiments.
[0037] The following describes examples of components of a lead-acid battery.
[0038] (lead acid battery) The lead-acid battery according to this disclosure can more significantly improve the deep discharge life in liquid-type batteries (vented batteries) where softening and detachment of the positive electrode material are prone to occur. However, the lead-acid battery according to this disclosure may also be a valve-regulated lead-acid battery (VRLA type battery).
[0039] A lead-acid battery comprises a positive electrode plate, a negative electrode plate, a separator interposed between the positive and negative electrode plates, and an electrolyte. The electrolyte contains sulfuric acid. Charging and discharging proceed through the movement of sulfate ions between the positive and negative electrode plates and the electrolyte. During discharge, sulfate ions move to the positive and negative electrode plates. During charging, sulfate ions move from the positive and negative electrode plates into the electrolyte.
[0040] A positive electrode plate, a negative electrode plate, and a separator constitute an electrode group. The electrode group, together with the electrolyte, constitutes a cell. One electrode group constitutes one cell. A lead-acid battery comprises one or more cells by comprising one or more electrode groups. There is no particular limit to the number of positive and negative electrode plates included in one electrode group. An electrode group comprising a lead-acid battery according to this disclosure may, for example, include a total of 12 or more positive and negative electrode plates. Multiple electrode groups are typically housed in separate cell chambers and connected in series with one another.
[0041] The positive electrode plate includes a positive electrode material. The positive electrode material, as a positive electrode active material that exhibits capacity through oxidation-reduction reactions, contains at least lead dioxide during charging and at least lead sulfate during discharge.
[0042] The negative electrode plate includes a negative electrode material. The negative electrode material is a negative electrode active material that exhibits capacity through an oxidation-reduction reaction, and contains at least lead during charging and at least lead sulfate during discharging.
[0043] In this specification, the fully charged state of a liquid lead-acid battery is defined according to the definition in JIS D 5301:2019. More specifically, the 20-hour rate current I is used until the terminal voltage (in volts) during charging, measured every 15 minutes in a 25°C ± 2°C water bath, or the electrolyte density converted to a temperature of 20°C, shows a constant value with three significant figures for three consecutive times. 20 Twice the current 2I 20 (Unit: A) The fully charged state of a lead-acid battery is defined as the state in which it has been charged. Note that the 20-hour rate current I 20This refers to a current (A) that is 1 / 20th of the Ah value listed in the rated capacity. The value listed as the rated capacity is a value in Ah (ampere-hour). The unit of the current set based on the value listed as the rated capacity is A (ampere).
[0044] Furthermore, in the case of a valve-regulated lead-acid battery, a fully charged state is defined as a 20-hour rate current of 1 in an air chamber at 25°C ± 2°C. 20 5 times the current 5I 20 The battery was then charged at a constant current and voltage of 2.67V / cell (16.00V for a lead-acid battery with a nominal voltage of 12V), and the charging process was terminated when the total charging time reached 24 hours.
[0045] A fully charged lead-acid battery is a lead-acid battery that has been charged to its full capacity after chemical formation. The timing for charging a lead-acid battery to its full capacity can be immediately after chemical formation, or after a certain amount of time has passed since formation (e.g., 720 hours or less). For example, a lead-acid battery that has been chemically formed and is in use (preferably in the early stages of use) may be charged.
[0046] In this specification, a battery in its initial use refers to a battery that has not been used for very long and has not deteriorated much (for example, a battery that has been in use for less than 720 hours, including the time elapsed since chemical preparation).
[0047] (Positive plate) The positive electrode plate comprises a positive electrode current collector and a positive electrode material. The positive electrode material is held by the positive electrode current collector. The positive electrode material is the portion of the positive electrode plate excluding the positive electrode current collector. Adhesive members such as conductive layers, mats, and pasting paper may be attached to the positive electrode plate. Since the adhesive members are used integrally with the positive electrode plate, they are included as components of the positive electrode plate. When the positive electrode plate includes adhesive members, the positive electrode material is the portion of the positive electrode plate excluding the positive electrode current collector and the adhesive members.
[0048] The positive electrode current collector may be formed by casting lead (Pb) or a lead alloy, or by processing a lead or lead alloy sheet. Processing methods may include, for example, expansion or punching. Using a grid-like current collector as the positive electrode current collector makes it easier to support the positive electrode material.
[0049] As the lead alloy used for the positive electrode current collector, Pb-Ca alloys and Pb-Ca-Sn alloys, which have excellent corrosion resistance and mechanical strength, are preferred. The positive electrode current collector may have metal layers of different compositions, and the metal layers may be one layer or multiple layers.
[0050] The positive electrode material includes a positive electrode active material that exhibits capacity through a redox reaction. The positive electrode active material includes lead dioxide, lead sulfate, etc. The positive electrode material also includes fibers as a reinforcing material and may include antimony compounds, etc., as needed.
[0051] The average surface roughness Ra of the fibers is preferably between 0.1 μm and 1.3 μm. In this case, it is easier to form irregularities on the fiber surface that enhance the anchoring effect, and oxidative degradation of the fibers by the positive electrode material is suppressed.
[0052] The average surface roughness Ra of the fibers is determined from fibers taken from the positive electrode material of a fully charged lead-acid battery using the same procedure as described above (method for measuring the maximum surface height Rz of the fibers).
[0053] The fiber has a BET specific surface area measured using krypton gas as the adsorbent gas, for example, 0.3 m². 2 / g or more 1.0m 2 It may be less than / g. The BET specific surface area of the fiber measured using krypton gas as the adsorbent gas is 0.3m². 2 When the value is 1 / g or higher, it is easier to ensure even better lifespan performance. In addition, the BET specific surface area of the fiber measured using krypton gas as the adsorbent gas is 1.0 m². 2 When the value is less than / g, the oxidation resistance of the fibers improves, and the positive electrode plate can more easily ensure sufficient conductivity.
[0054] The BET specific surface area of fibers measured using krypton gas as the adsorption gas is determined for fibers taken from the positive electrode material of a fully charged lead-acid battery. For the fiber samples for analysis obtained by the procedure described below, the BET specific surface area is determined using krypton gas as the adsorption gas, in accordance with the calculation method for BET specific surface area in JIS Z 8830:2013, 7.2.
[0055] The BET specific surface area of a fiber may be adjusted, for example, by surface treatment of the fiber, as well as by adjusting the maximum surface height Rz (and average roughness Ra) of the fiber. Alternatively, the maximum surface height Rz (and average roughness Ra) and the BET specific surface area of the fiber may be adjusted simultaneously by surface treatment of the fiber. As methods for treating the fiber surface, the methods described above can be used, for example, chemical treatment, plasma treatment, corona treatment, UV irradiation treatment, and sandblasting treatment.
[0056] The fiber content in the positive electrode material may be, for example, 0.05% by mass or more and 0.23% by mass or less. When the fiber content in the positive electrode material is 0.05% by mass or more, the effect of the fibers is fully realized, and even better life performance can be ensured. Also, when the fiber content in the positive electrode material is 0.23% by mass or less, the fiber content in the positive electrode material is appropriate, and the conductivity of the positive electrode plate becomes even better.
[0057] The effect of suppressing softening and shedding by fibers can also depend on the material of the fibers. Preferably, the fibers are made of a resin that is thin yet strong and stable in the presence of sulfuric acid.
[0058] The resin constituting the fiber may be polyester, polyolefin, polystyrene, polyvinyl chloride, acrylic resin, etc. Among these, at least one selected from the group consisting of polyester and polyolefin is preferred because of its excellent acid and alkali resistance. Examples of polyester include polyalkylene arylates such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT). Examples of polyolefins include polyethylene, polypropylene (PP), and ethylene-propylene copolymer. The fiber may contain one of these resins or two or more. Furthermore, the positive electrode material may contain multiple fibers composed of different resins.
[0059] In particular, using PET makes it easier to improve the deep discharge life of lead-acid batteries. PET has excellent acid resistance and mechanical strength. Therefore, fibers made of PET have a fine average fiber diameter, and even a small amount can secure a large surface area, which has a significant effect on improving the deep discharge life of lead-acid batteries. Furthermore, PET fibers are inexpensive.
[0060] For example, 85% or more of the fiber may be composed of polyester. Fibers containing such a high percentage of polyester are usually called polyester fibers (e.g., PET fibers). Also, 85% or more of the fiber may be composed of polyolefin. Fibers containing such a high percentage of polyolefin are usually called polyolefin fibers (e.g., polyethylene fibers, polypropylene fibers). Similarly, fibers in which 85% or more of the fiber is composed of acrylic resin are called acrylic fibers.
[0061] The type of resin constituting the fibers contained in the positive electrode material can be identified by analyzing the fibers recovered from the positive electrode material using the method described in JIS L 1030-1:2024. The fibers may be recovered by pulling them out of the positive electrode material with tweezers, or they may be recovered from the residue after dissolving the lead compound contained in the positive electrode material, as described below.
[0062] The positive electrode material is recovered from the positive electrode plate by the following procedure. First, a fully charged lead-acid battery is disassembled, and the obtained positive electrode plate is washed with water for 3 to 4 hours to remove the electrolyte from the positive electrode plate. The washed positive electrode plate is dried in a constant temperature bath at 60°C ± 5°C for 5 hours or more. A bonding material containing fibers and / or a nonwoven fabric separator may be attached to the positive electrode plate. The fibers contained in the bonding material and nonwoven fabric must be distinguished from the fibers used as reinforcing material. If a bonding material and / or nonwoven fabric is attached to the positive electrode plate, the surface of the positive electrode plate is scraped off until any residue of the bonding material and / or nonwoven fabric is removed, and then the positive electrode material is collected. For example, the surface layer on both sides of the positive electrode plate may be scraped evenly before collecting the positive electrode material. In this case, it is desirable to scrape to a depth of about 0.1 mm to 0.3 mm on each side. Next, a sample of the positive electrode material for analysis is taken from near the center of the positive electrode plate when viewed from the front, without crushing it.
[0063] The fibers are recovered from the positive electrode material sample by the following procedure. First, a predetermined amount Wg (e.g., about 70g) of positive electrode material sample is crushed and accurately weighed. At this time, the positive electrode material contained in one or more positive electrode plates may be used as the sample.
[0064] Next, the pulverized sample is added to a mixed solution of acetic acid-sodium acetate solution and sodium thiosulfate solution (acetic acid concentration 1.7 mol / L, sodium acetate concentration 6.1 mol / L, sodium thiosulfate concentration 0.5 mol / L), and the soluble components are dissolved while stirring at room temperature. After that, it is washed with deionized water. Then, the resulting residue is filtered using a membrane filter (average pore size: 0.45 μm or less). This allows the fibers contained in the positive electrode material to be obtained as solid matter on the filter paper.
[0065] A fiber sample for analysis is obtained by washing and drying the resulting solid. The mass w (g) of the fiber sample is measured. The percentage of the mass w (g) of the fiber sample relative to the mass W (g) of the positive electrode material sample is the fiber content in the positive electrode material.
[0066] The resin constituting the fibers can be identified by analyzing the infrared absorption spectrum of the fiber sample. Method B (film method) specified in JIS L 1030-1:2024 may be used as the analytical method.
[0067] Specifically, the fiber sample is dissolved in an appropriate dissolving reagent (see Table A), poured into an evaporating dish, and dried under vacuum or by heating to a temperature that does not decompose the sample. Next, the dried film is peeled off without tearing, cut to an appropriate size, and the infrared absorption spectrum is measured in accordance with JIS K 0117:2017. The film should be of a thickness that makes it transparent. Also, the size of the film will vary depending on the infrared spectrophotometer used, so it should be at least 1 cm. 2 That concludes this section.
[0068] Table A exemplifies the main absorption bands and characteristic wavenumbers of the infrared absorption spectra of various fibers, as well as the dissolving reagents. The absorption bands and characteristic wavenumbers of each fiber vary by ±20 cm depending on the infrared spectrophotometer used. -1 There are differences in degree.
[0069] [Table A]
[0070] The average fiber diameter D of the fibers may be, for example, 20 μm or less, but may also be 13 μm or less, 10 μm or less, 9 μm or less, or 8 μm or less. The average fiber diameter D of the fibers may also be, for example, 1 μm or more, 4 μm or more, or 6 μm or more. The average fiber diameter D of the fibers is, for example, 1 μm to 20 μm, but may also be 1 μm to 13 μm, 4 μm to 20 μm, 1 μm to 10 μm, 1 μm to 9 μm, 1 μm to 8 μm, 4 μm to 13 μm, 4 μm to 10 μm, 4 μm to 9 μm, 4 μm to 8 μm, 6 μm to 20 μm, 6 μm to 13 μm, 6 μm to 10 μm, or 6 μm to 9 μm. Such fibers maintain sufficiently high mechanical strength and can have a large specific surface area. Furthermore, even with the same amount of fiber, the number of fibers increases, making it easier for the fibers to be interwoven within the positive electrode material. Therefore, the contact area between the fibers and the positive electrode material becomes sufficiently large, and the reinforcing effect of the fibers is significantly realized.
[0071] The average fiber diameter D of a fiber is determined by selecting any 20 fibers from a fiber sample, measuring the fiber diameter (the dimension perpendicular to the length of the fiber) at any point on each fiber, and taking the arithmetic mean of the measurements. The average fiber diameter D of a fiber may also be measured using a scanning electron microscope (SEM) image of the fiber.
[0072] Unformed paste-type positive electrode plates are obtained by filling a positive electrode current collector with positive electrode paste, followed by maturation and drying. The positive electrode paste is prepared by kneading lead powder, and optionally additives (such as reinforcing materials), with water and sulfuric acid.
[0073] A positive electrode plate can be obtained by chemically treating an untreated positive electrode plate. Chemical treatment can be carried out by immersing the electrode plate group, including the untreated positive electrode plate, in an electrolyte containing sulfuric acid in the battery case of a lead-acid battery, and then charging the electrode plate group. However, chemical treatment may also be carried out before the assembly of the lead-acid battery or the electrode plate group.
[0074] (Negative electrode plate) The negative electrode plate of a lead-acid battery consists of a negative electrode current collector and a negative electrode material. The negative electrode material is the portion of the negative electrode plate excluding the negative electrode current collector. In some cases, an adhesive member may be attached to the negative electrode plate. In this case, the adhesive member is included in the negative electrode plate. When the negative electrode plate includes an adhesive member, the negative electrode material is the portion of the negative electrode plate excluding the negative electrode current collector and the adhesive member.
[0075] The negative electrode current collector included in the negative electrode plate may be formed by casting lead (Pb) or a lead alloy, or by processing a lead or lead alloy sheet. Examples of processing methods include expanding or punching. Using a grid-shaped current collector as the negative electrode current collector is preferable because it makes it easier to support the negative electrode material.
[0076] The lead alloy used for the negative electrode current collector may be any of the following: a Pb-Sb alloy, a Pb-Ca alloy, or a Pb-Ca-Sn alloy. The lead alloy used for the negative electrode current collector may also contain at least one additive element selected from the group consisting of Ba, Ag, Al, Bi, As, Se, Cu, etc. The negative electrode current collector may have lead alloy layers of different compositions, and the alloy layer may be a single layer or multiple layers.
[0077] The negative electrode material contains a negative electrode active material that exhibits capacity through a redox reaction. The negative electrode active material includes lead, lead sulfate, etc. The negative electrode material may contain other additives as needed. The additives may include organic shrinkage inhibitors, carbonaceous materials, barium sulfate, etc.
[0078] Examples of organic shrinkage inhibitors include lignin, lignin sulfonic acid, and synthetic organic shrinkage inhibitors (such as formaldehyde condensates of phenol compounds). Organic shrinkage inhibitors may be used individually or in combination of two or more. The content of the organic shrinkage inhibitor in the negative electrode material is, for example, 0.01% by mass or more. The content of the organic shrinkage inhibitor is, for example, 1.2% by mass or less.
[0079] Examples of carbonaceous materials include carbon black, graphite, hard carbon, and soft carbon. A single carbonaceous material may be used, or two or more may be used in combination. The carbonaceous material content in the negative electrode material is, for example, 0.1% by mass or more. Alternatively, the carbonaceous material content may be, for example, 3.5% by mass or less.
[0080] The barium sulfate content in the negative electrode material is, for example, 0.1% by mass or more and 3% by mass or less.
[0081] Examples of reinforcing materials include fibers (inorganic fibers, organic fibers, etc.). The reinforcing material content in the negative electrode material is, for example, 0.03% by mass or more. Alternatively, the reinforcing material content in the negative electrode material is, for example, 0.6% by mass or less.
[0082] The negative electrode plate can be formed by filling a negative electrode current collector with negative electrode paste, aging and drying it to produce an unformed negative electrode plate, and then forming the unformed negative electrode plate. The negative electrode paste is made by kneading lead powder, an organic shrinkage inhibitor, barium sulfate, etc., with water and sulfuric acid. The negative electrode active material in the charged state is spongy lead, but the unformed negative electrode plate is usually made using lead powder. In the aging process, it is preferable to age the unformed negative electrode plate at a temperature higher than room temperature and at high humidity.
[0083] The chemical conversion can be carried out by immersing the electrode plate group, including the unconverted negative electrode plate, in the sulfuric acid-containing electrolyte in the lead-acid battery case and then charging the electrode plate group. However, the chemical conversion may also be performed before the assembly of the lead-acid battery or the electrode plate group. Spongy lead is produced by the chemical conversion.
[0084] (Separator) As a separator placed between the negative electrode plate and the positive electrode plate, at least one selected from, for example, nonwoven fabric and microporous membrane can be used.
[0085] Nonwoven fabrics are mats composed of interwoven fibers rather than woven fibers, and are primarily fiber-based. For example, 60% or more of the nonwoven fabric is made up of fibers. Suitable fibers include glass fibers, polymer fibers (polyolefin fibers, acrylic fibers, polyester fibers (such as polyethylene terephthalate fibers), etc.), and pulp fibers. Glass fibers are preferred among these. Nonwoven fabrics may also contain other components besides fibers, such as acid-resistant inorganic powders and polymers as binders.
[0086] A microporous membrane is a porous sheet mainly composed of materials other than fibrous components. For example, it can be obtained by extruding a composition containing a pore-forming agent into a sheet, and then removing the pore-forming agent to form pores. Preferably, the material other than fibrous components is 60% by mass or more. The microporous membrane is preferably composed of acid-resistant materials, and preferably mainly composed of polymer components. As the polymer component, polyolefins (polyethylene, polypropylene, etc.) are preferred. Examples of pore-forming agents include polymer powders and oils.
[0087] The separator may consist solely of a nonwoven fabric, or solely of a microporous membrane. The separator may also be a laminate of a nonwoven fabric and a microporous membrane, a laminate of different or the same type of material bonded together, or a laminate of different or the same type of material with interlocking protrusions and indentations.
[0088] The separator may be in the form of a sheet or a bag. A single sheet-shaped separator may be placed between the positive and negative electrodes. The electrode plates may be sandwiched between folded sheet-shaped separators. The positive electrode sandwiched between folded sheet-shaped separators and the negative electrode sandwiched between folded sheet-shaped separators may be stacked on top of each other, or one of the positive and negative electrodes may be sandwiched between folded sheet-shaped separators and stacked on top of the other electrode plate. When a bag-shaped separator is used, the bag-shaped separator may contain either the positive electrode or the negative electrode.
[0089] The thickness of the separator placed between the negative electrode plate and the positive electrode plate should be selected according to the distance between the two plates.
[0090] (electrolyte) The electrolyte is an aqueous solution containing sulfuric acid. The electrolyte may be gelled as needed. The electrolyte may optionally contain cations (e.g., metal cations) and / or anions (e.g., phosphate ions) not derived from sulfuric acid. Examples of metal cations include at least one selected from the group consisting of Na ions, Li ions, Mg ions, and Al ions.
[0091] The specific gravity of the electrolyte in a fully charged lead-acid battery at 20°C is, for example, 1.10 or higher. The specific gravity of the electrolyte at 20°C may also be 1.35 or lower. These specific gravity values are for the electrolyte in a fully charged lead-acid battery.
[0092] The matters described herein can be combined in any way.
[0093] (Example of a lead-acid battery) Figure 1 shows the external appearance and part of the internal structure of a lead-acid battery according to one embodiment. The lead-acid battery 1 comprises a battery case 12 that houses an electrode plate group 11 and an electrolyte (not shown). The inside of the battery case 12 is divided into a number of cell chambers 14 by a partition wall 13. Each cell chamber 14 houses one electrode plate group 11. The opening of the battery case 12 is closed with a lid 15 equipped with a negative electrode terminal 16 and a positive electrode terminal 17. The lid 15 is provided with a vent plug 18 for each cell chamber. When replenishing water, the vent plug 18 is removed and the water is replenished. The vent plug 18 may also have a function of discharging gas generated in the cell chamber 14 to the outside of the battery.
[0094] Each electrode plate group 11 is constructed by stacking multiple negative electrode plates 2 and positive electrode plates 3 via separators 4. Here, a bag-shaped separator 4 that houses the negative electrode plates 2 is shown, but the shape of the separator is not particularly limited. In the cell chamber 14 located at one end of the battery case 12, a negative electrode strap 6 connecting multiple negative electrode plates 2 in parallel is connected to a through connector 8, and a positive electrode strap 5 connecting multiple positive electrode plates 3 in parallel is connected to a positive electrode column 7. The positive electrode column 7 is connected to a positive electrode terminal 17 on the outside of the lid 15. In the cell chamber 14 located at the other end of the battery case 12, a negative electrode column 9 is connected to the negative electrode strap 6, and a through connector 8 is connected to the positive electrode strap 5. The negative electrode column 9 is connected to a negative electrode terminal 16 on the outside of the lid 15. Each through connector 8 passes through a through hole provided in the partition wall 13, connecting the electrode plate groups 11 of adjacent cell chambers 14 in series.
[0095] Note that Figure 1 is merely one example of a liquid-type lead-acid battery, and the structure of the lead-acid battery relating to this disclosure is not limited to the example shown.
[0096] (Examples) The present invention will be described in detail below based on examples and comparative examples, but the present invention is not limited to the following examples. Here, a liquid lead-acid battery with a nominal voltage of 12V and a 20-hour rate capacity of 30Ah is assembled. The 20-hour rate capacity is the capacity when discharged at a current (A) of 1 / 20 of the Ah value stated in the rated capacity. The evaluation method will be described below. Note that the current (A) which is 1 / n of the Ah value listed in the rated capacity is the n-hour rate current (I n ) is called. n This is the current value (in A) that corresponds to the value obtained by dividing the battery's rated n-hour rate capacity (in Ah) by n. Therefore, I 20 (20-hour rate current) is the current (A) that is 1 / 20th of the Ah value listed in the rated capacity.
[0097] (Life Test Method) The deep discharge life (50% DOD) is evaluated in accordance with JIS D 5301:2019. Here, a fully charged lead-acid battery is repeatedly discharged and charged under the following conditions, and the number of cycles until the deep discharge life is reached is evaluated.
[0098] The life test will be conducted according to the following steps (a) to (d).
[0099] a) Charging: Fully charge the lead-acid battery using the method described above. b) Installation: Place the lead-acid battery in a water tank at 25±2℃. The water level should be 15mm to 25mm above the top of the lead-acid battery. Water can be added as needed using distilled water. c) Charging and discharging: Connect the lead-acid battery to the life test device and repeat the cycle described below. 1) Discharge: 5×I 20 Discharge for 2 hours. 2) Charging: 15.6V ± 0.03V (limiting current 5 × I 20 Charge for 5 hours. Stop charging when the ratio CR (2 × charge amount / 20-hour rate capacity) of the amount of charge to the 20-hour rate capacity reaches 1.1 or higher. 3) If CR is 1.1 or less, constant current 2.5 × I 20 Charge until the CR ratio reaches 1.1. However, the charging time should be limited to a maximum of 1 hour. d) The test shall be terminated when the voltage in test c) becomes 10.5V or less.
[0100] (Capacity Test Method) The capacity retention rate of a lead-acid battery will be evaluated by repeatedly discharging and charging it under the following conditions.
[0101] After repeating the charge-discharge cycle under condition (i) below for 20 cycles at 40°C, perform the capacity test under condition (ii) below at 25°C. The ratio of the discharge capacity in the capacity test under condition (ii) after 40 charge-discharge cycles under condition (i) to the initial discharge capacity is calculated as the capacity retention rate as follows. Capacity retention rate (%) = (Discharge capacity after 40 cycles / Initial discharge capacity) × 100
[0102] (Condition (i)) (40℃) Discharge:I 20 Discharge for 1.5 hours Charging:I 20 After charging for 1.2 hours, continue with 0.15 × I 20 5.5 hours to charge
[0103] (Condition (ii)) (25℃) Discharge:I 20 (Discharge termination voltage (FV) = 1.8V / cell) Charging:I 20 This charges 135% of the discharged electricity.
[0104] (Batteries E1~E34, batteries C1~C5) (1) Fabrication of the positive electrode plate A positive electrode paste is prepared by mixing lead oxide, fibers, water, and sulfuric acid. At this time, the predetermined amount of fibers is included in the positive electrode paste so that the maximum surface height Rz of the fibers taken from a fully charged battery and the surface area of the fibers per gram (S( / 1g)) of the positive electrode material taken from a fully charged battery, as measured by the procedure described above, are as shown in Table 1. The average fiber diameter of the fibers measured by the procedure described above is as shown in Table 1. The positive electrode paste is filled into the mesh of an expanded grid, which is a positive electrode current collector made of lead alloy, and cured and dried to obtain an unformed positive electrode plate with a width of 100 mm, a height of 110 mm, and a thickness of 1.6 mm.
[0105] The resins that make up the fibers used in the positive electrode paste are as follows: PET is used for batteries E1-E24, E28-E34, and C1-C2. PE is used for batteries E25 and C5. Use PU for batteries E26~E27. The C3 battery uses acrylic resin. The C4 battery uses vinylon.
[0106] "PET" refers to polyethylene terephthalate fiber, "PE" refers to polyethylene fiber, "PU" refers to polyurethane fiber, "acrylic" refers to acrylic fiber, and "vinylon" refers to synthetic fiber obtained by acetalizing polyvinyl alcohol.
[0107] (2) Fabrication of the negative electrode plate A negative electrode paste is prepared by mixing lead oxide, carbon black, barium sulfate, lignin, water, and sulfuric acid. The negative electrode paste is filled into the mesh of an expanded grid made of a Pb-Ca-Sn alloy, which serves as the negative electrode current collector, and then aged and dried to obtain an unformed negative electrode plate with a width of 100 mm, a height of 110 mm, and a thickness of 1.3 mm.
[0108] The amounts of carbon black, barium sulfate, and lignin used are adjusted so that the content of each component in the negative electrode plate removed from a fully charged lead-acid battery is 0.3% by mass, 2.1% by mass, and 0.1% by mass, respectively.
[0109] (3) Manufacturing of lead-acid batteries Untreated negative electrode plates are housed in a bag-shaped separator made of a microporous polyethylene membrane, and stacked with positive electrode plates to form an electrode plate group consisting of seven untreated negative electrode plates and six untreated positive electrode plates.
[0110] Positive and negative electrode trays are provided using a cast-on-strap (COS) method, connecting the tabs of the positive and negative electrode plates, respectively. The six electrode plates are inserted into a polypropylene battery case, connected in series, and electrolyte is poured in. A chemical conversion is then performed within the battery case to assemble a liquid lead-acid battery with a nominal voltage of 12V and a 20-hour rate capacity of 30Ah.
[0111] A sulfuric acid solution is used as the electrolyte. The density of the electrolyte after chemical conversion at 20°C is 1.285 g / cm³. 3 That is the case.
[0112] (4) Evaluation The obtained lead-acid batteries are evaluated by performing life tests and capacity tests according to the procedure described above. Table 1 shows the relative values (%) for deep discharge life and capacity retention rate (%) for each example. The relative values (%) are relative to the deep discharge life and capacity retention rate of battery C2, which is set to 100%.
[0113] [Table 1]
[0114] Table 1 shows that batteries E1 to E34, whose maximum fiber surface height Rz is between 0.17 μm and 1.9 μm, can achieve a better deep discharge life compared to batteries C1 to C5, whose maximum fiber surface height Rz is between 0.17 μm and 1.9 μm. This is thought to be because the charge-discharge reaction is less inhibited by the fibers, and a high anchoring effect is also exhibited. In particular, the results for batteries E1 to E5 show that an even better deep discharge life can be achieved when the maximum fiber surface height Rz is between 0.6 μm and 1.4 μm.
[0115] Based on the results for batteries E3, E6, and E9, when comparing batteries with the same maximum height Rz, the surface area of the fibers per gram of positive electrode material (S( / 1g)) is 1.35 cm². 2 Compared to the E6 battery, which has a weight of less than 1.35 cm², S( / 1g) is 1.35 cm². 2 As shown above, batteries E3, E7-E9 exhibit good deep discharge life. This is thought to be because the large contact area allows the fibers and lead compound to intertwine, resulting in a higher anchoring effect from the fibers.
[0116] Furthermore, it can be seen that while battery C1 maintains a good capacity retention rate, its deep discharge life characteristics are unfavorable. This is thought to be because, although the maximum surface height Rz of the fibers is less than 0.17 μm, the charge-discharge reaction is not easily inhibited by the fibers, but a sufficient anchoring effect is not obtained.
[0117] Based on the results for batteries C1 to C5, it is considered that when the maximum surface height Rz of the fibers exceeds 1.9 μm, the capacity retention rate tends to decrease as the surface area of fibers per gram of positive electrode material (S( / 1g)) increases. On the other hand, a comprehensive assessment of Table 1 shows that when the maximum surface height Rz of the fibers is less than 1.9 μm, the decrease in capacity retention rate is suppressed even if the surface area of fibers per gram of positive electrode material (S( / 1g)) increases. In particular, when the maximum surface height Rz of the fibers is between 0.17 μm and 1.4 μm, the decrease in capacity retention rate when the surface area of fibers per gram of positive electrode material (S( / 1g)) increases is significantly suppressed. [Industrial applicability]
[0118] The lead-acid battery according to this disclosure is suitable, for example, as a lead-acid battery for vehicles employing a start-stop system, and can also be suitably used as a power source for industrial energy storage devices such as electric vehicles (forklifts, etc.). These applications are merely examples. The applications of the lead-acid battery according to the present invention are not limited to these. [Explanation of Symbols]
[0119] 1: Lead-acid battery, 2: Negative electrode plate, 3: Positive electrode plate, 4: Separator, 5: Positive electrode shelf, 6: Negative electrode shelf, 7: Positive electrode column, 8: Through connector, 9: Negative electrode column, 11: Electrode plate group, 12: Battery case, 13: Partition wall, 14: Cell chamber, 15: Cover, 16: Negative electrode terminal, 17: Positive electrode terminal, 18: Electrode cap
Claims
1. It comprises a positive electrode plate, a negative electrode plate, an electrolyte, and a separator interposed between the positive electrode plate and the negative electrode plate. The positive electrode plate includes a positive electrode material, The positive electrode material includes fibers, A lead-acid battery in which the maximum surface height Rz of the aforementioned fibers is 0.17 μm or more and 1.9 μm or less.
2. The surface area of the fibers per gram of the positive electrode material is 1.35 cm². 2 The lead-acid battery according to claim 1.
3. The lead-acid battery according to claim 1, wherein the maximum surface height Rz of the fiber is 1.4 μm or less.
4. The lead-acid battery according to claim 1, wherein the average fiber diameter of the aforementioned fibers is 1 μm or more and 9 μm or less.
5. The surface area of the fibers per gram of the positive electrode material is 3.00 cm². 2 The lead-acid battery according to claim 1.
Citation Information
Patent Citations
Lead storage battery
JP2019067741A